Temperaments - Hofstadter, Dan (Open Road Distribution, 2015)
In these five profiles, four of which originally appeared in the New Yorker, the author evokes the life and work of seven gifted artists. Among those presented, often through lively conversations, are Jean Hélion, Mark Rothko, R.B. Kitaj, and Dennis Creffield. Chief among those portrayed however is Henri Cartier-Bresson (1908-2004), the great French photographer and photojournalist who, famed for dodging contact with the press, is here sketched in rare and fond detail. Of all these artists, only two still live: what emerges from this book is a picture, often bizarre, often hilarious, of a bygo.